The optimization growth of Dracocephalum forrestii in RITA® bioreactor, and preliminary screening of the biological activity of the polyphenol rich extract - Izabela Weremczuk-Jeżyna; Liwia Lebelt; Dorota Piotrowska; Weronika Gonciarz; Magdalena Chmiela; Izabela Grzegorczyk-Karolak (Acta Scientiarum Polonorum: Hortorum Cultus, 2023)
Dracocephalum forrestii is a medicinal plant growing in China. The aim of the present study was to large-scale cultivation of D. forrestii transformed shoots in a temporary immersion system based on previously-optimized Murashige and Skoog (MS) medium supplemented with 0.5 mg/L N-benzyl-9-(2-tetrahydropyranyl)-adenine (BPA) and 0.2 mg/L indole-3-acetic acid (IAA) and physical (under blue LED) conditions. Shoot proliferation, and biomass and secondary metabolite accumulation in the shoots were assessed after a three-week growth period in a RITA® bioreactor. The levels of polyphenols in four types of extract (hydromethanolic extracts – mixtures with a 20%, 50%, and 80% methanol content and infusion) were determined using high-performance liquid chromatography (HPLC). Within three weeks, the culture increased its biomass 283-fold, with a proliferation ratio of 40.5 shoots or/and buds per explants. The most efficient solvent for extraction of phenolic compounds from raw material turned out to be 80% methanol solution; the highest polyphenol content was 40 mg/g DW (dry weight) with acacetin rhamnosyl-trihexoside (12.97 mg/g DW) and rosmarinic acid (10.68 mg/g DW) predominating. The intensive growth of the biomass of the culture allowed 570 mg of polyphenolic compounds to be obtained per liter of the medium. The antioxidant potential of extract of D. forrestii shoots was evaluated using three free radical-scavenging tests, and the inhibition of lipid peroxidation assay. In the study, the cytotoxic, antibacterial and antifungal potentials of the extract were also determined.